Lama Penyimpanan, Karakterisasi Fisiologi, dan Viabilitas Bakteri Endofit Bacillus sp. dalam Formula Tepung - Diana putri; Abdul Munif; Kikin Hamzah Mutaqin (Jurnal Fitopatologi Indonesia, 2016)
Endophytic bacteria can be formulated to retain its ability as disease control agents. Three of endophytic bacteria which had the capability to suppress infection of Meloidogyne sp, and to enhance pepper growth were gained from the previous study. This research was aimed to evaluate the influence of storage time on the viability of endophytic bacteria, Bacillus sp. AA2, Bacillus sp. MER and MSJ, and to study its physiological charaterization during storage. The formulation evaluated in this study was : formulation 1 (50 g talc, 1 g pepton, 0.5 g CMC, and brown sugar 1.5 g), formulation 2 (50 g talc, 1 g pepton, 0.5 g CMC, and 1.5 g white sugar), formulation 3 (50 g talc, 1 g pepton, 0.5 g CMC, 1 g yeast extract, and 1.5 gwhite sugar) and formulation 4 (50 g talc, 1 g pepton, 0.5 g CMC, 1 g yeast extract, 3 mL molasses, 1 gbentonite, 0.75 g calcium carbonate, and 1 g dextrose). The results of the bacterial characterization showed that Bacillus sp AA2 and Bacillus sp MER belongs to Gram positive, produced lipase and protease enzyme, as well as  IAA hormone. N2 fixation is only existed in Bacillussp. AA2 and MSJ isolate. The highest viability was shown on MSJ isolate with 2.5×106 cfu mL-1. in the fourth formulation, whereas Bacillus sp. AA2 and Bacillus sp. MER viability was 1.9×106 cfu mL-1. and 1.2×106 cfu mL-1. , respectively.